Optimal Control Application in Mathematical Model of Indonesian Coffee Export Tax - Melyana, Nanda; Syahrini, intan; Munzir, Said (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Coffee is one of Indonesia's largest non-oil and gas export commodities in the agricultural sector, significantly contributing to the country's export volume each year. Major export destinations include the United States, Egypt, Japan, Spain, and Malaysia. Approximately 67% of Indonesia's coffee production is exported, while the remaining 33% serves domestic demand. To optimize the economic values related to production, demand, export volume, and export tax revenue, a dynamic model was developed, followed by two simulations: one where the government controls with set economic targets and another without target controls on export tax. The model formulation involved estimating equations using the Two-Stage Least Squares (TSLS) method, which served as constraints within the optimal control model. The objective of the discrete dynamic optimal control function is to minimize a quadratic objective function that represents deviations from target values and optimal control levels. Simulations conducted with varying weights on both the control function and without governmental intervention showed that changes in the export tax have limited impact on final outcomes, likely due to the high export tax rate applied. It is recommended that, to achieve export tax values closer to desired targets, the government could consider adjusting export tariff policies by reducing the export tax rate, which would also encourage increased export volume. @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-469750017 -1073732485 9 0 511 0;}@font-face {font-family:Cambria; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1073743103 0 0 415 0;}@font-face {font-family:"Baskerville Old Face"; panose-1:2 2 6 2 8 5 5 2 3 3; mso-font-charset:77; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;}p.IOP-CS-Abstract, li.IOP-CS-Abstract, div.IOP-CS-Abstract {mso-style-name:IOP-CS-Abstract; mso-style-unhide:no; mso-style-qformat:yes; mso-style-link:"IOP-CS-Abstract Char"; margin-top:0cm; margin-right:0cm; margin-bottom:18.0pt; margin-left:70.9pt; text-align:justify; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Cambria",serif; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-font-kerning:1.0pt; mso-ligatures:standardcontextual; mso-ansi-language:EN-GB;}span.IOP-CS-AbstractChar {mso-style-name:"IOP-CS-Abstract Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:IOP-CS-Abstract; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Cambria",serif; mso-ascii-font-family:Cambria; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-font-kerning:1.0pt; mso-ligatures:standardcontextual; mso-ansi-language:EN-GB;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-font-kerning:0pt; mso-ligatures:none; mso-ansi-language:EN-US;}div.WordSection1 {page:WordSection1;}